Solution‐Crystalized AgBiS2 Films for Solar Cells Generating a Photo‐Current Density Over 31 mA cm−2 - Ludmila Cojocaru; Ajay Kumar Jena; Miwako Yamamiya; Youhei Numata; Masashi Ikegami; Tsutomu Miyasaka (Advanced Science, 2024)
Abstract In response to the toxic heavy metal absorbers in perovskite solar cells (PSCs), this work focuses on the development of an environmentally friendly simple solution‐processed infrared (IR) absorber. In this work, a simple solution‐crystallized IR‐absorbing AgBiS2 film is reported by spin‐coating silver, bismuth nitrates, and thiourea dissolved in dimethylformamide (DMF) to produce thick AgBiS2 film. Extensive optimization of the precursor concentrations thicknesses and conductive substrates used allow for obtaining 250 nm AgBiS2 film with different crystal sizes. When applied as an absorber in solar cells, solution‐crystalized AgBiS2 thick film delivers an extraordinarily high current density of over 31 mA cm−2. The devices show high stability under continuous 100 mW cm−2 illumination and when stored in the dark for more than six months. When the AgBiS2 layer is fabricated in a gradient fashion combining one layer of 0.25 m and three layers of 0.5 m precursor concentrations, the efficiency of 5.15% is registered which is the highest reported for the simple solution‐crystallized AgBiS2 films.